2022
DOI: 10.1007/s11756-022-01207-3
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial therapeutics isolated from algal source: retrospect and prospect

Abstract: In the last few decades, attention on new natural antimicrobial compounds has arisen due to a change in consumer preferences and the increase in the number of resistant microorganisms. Algae are defined as photosynthetic organisms that demonstrate a wide range of adaptability to adverse environmental conditions like temperature extremes, photo-oxidation, high or low salinity, and osmotic stress. Algae are primarily known to produce large amounts of secondary metabolite against various kinds of pathogenic micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 111 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…Several other studies reported similar results, extraction using ethanol solvents produced better tannin yields than other solvents [25][26][27] Low amounts of tannins added to bovine feed can improve rumen microbial function and have antioxidant and pathogenic antibacterial effects [22]. Tannin have an anti-microbial effect against several types of bacteria such as of E. coli O157:H7 [28], Bacillus subtilis, Salmonella Enteritica, Clostridium perfringens, and Staphylococcus aureus [26] . Tannins have also been reported to inhibit the growth of methanogenic bacteria [20,29] However, tannins become antinutritional factors at large concentrations, decreasing the ability of nutrients, particularly proteins and carbohydrats, to be digested [30] .…”
Section: Saponinmentioning
confidence: 78%
“…Several other studies reported similar results, extraction using ethanol solvents produced better tannin yields than other solvents [25][26][27] Low amounts of tannins added to bovine feed can improve rumen microbial function and have antioxidant and pathogenic antibacterial effects [22]. Tannin have an anti-microbial effect against several types of bacteria such as of E. coli O157:H7 [28], Bacillus subtilis, Salmonella Enteritica, Clostridium perfringens, and Staphylococcus aureus [26] . Tannins have also been reported to inhibit the growth of methanogenic bacteria [20,29] However, tannins become antinutritional factors at large concentrations, decreasing the ability of nutrients, particularly proteins and carbohydrats, to be digested [30] .…”
Section: Saponinmentioning
confidence: 78%
“…Living organisms produce various types of bioactive secondary metabolites to defend themselves against environmental threats and infection by microbial pathogens [49][50][51][52][53][54]. Bacteria also produce a variety of high-value chemicals, including the unique biological functions of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The algae emissions of volatile halocarbons and their impact on the environment are reviewed, 18 and the antimicrobial therapeutic potential of algae metabolites is outlined. 19…”
Section: ■ Marine Algaementioning
confidence: 99%